07 Being a Teacher in a Digital Era - Nadia Laura SERDENCIUC (Association of Social and Educational Innovation, 2016)
The present study focuses on a few of the teacher's responsibilities as an actor involved in the process of the personality development in the context of a digital world. A teacher's professional profile, that allows putting in a genuine correspondence the learning environment with the needs of 'digital natives', keeping at the same time a fair balance between the requirements of society and the perspectives of the personal development, is the one that can sustain a successful fulfilment of the teacher's mission in the contemporary society. Building a new teacher's profile based on: the resignification of the learning process, the new way of understanding the knowledge functioning and structure and the reflection upon the requirements of extended learning environments is not the responsibility of the educational systems only, but it requires also a social recognition and support in order to better address to the changes of global civilization.